Game-Based Science Learning: What are the Problems with Teachers Practicing It in Class? - Avdiu Schabas (CV. Bimbingan Belajar Assyfa, 2023)
Middle school science learning prioritizes class literacy through independent, integrated learning, only text, without any activity in the learning process. Contemporary literary studies show constant changes in the world of learning and teaching, and for many years, learning through play has been considered one of the most effective ways to learn something. This research aims to understand the pedagogical methods used in learning through play and the importance of these methods in the teaching process in elementary schools. This research involved five teachers from several secondary schools in Serbia: semi-structured interviews, researcher observation and class participation. The results of this research are based on descriptive analysis from the teacher's perspective. Based on the research results and researchers' comments, it can be understood that game-based learning in secondary schools in Austria is a popular pedagogy, creating a fun and adequate game-based learning context for children. In addition, the results of this study describe the activities carried out by the teacher, how the mechanism works, what the obstacles are, the solutions used in different subjects and the differences in the abilities and skills children develop through play. According to teachers, learning through play always poses challenges related to research, designing various play activities, and adapting learning to students' needs and interests